Home range estimates, habitat selection, and nesting behavior of Ferruginous Hawks (Buteo regalis) in western Wyoming - Ramirez, Sarah Kathleen, author; Pejchar, Liba, advisor; Koons, David, committee member; Angeloni, Lisa, committee member (Colorado State University. Libraries, 2024)
Oil and gas development has the potential to negatively impact wildlife, but the consequences for some raptor species are less well understood. Ferruginous Hawks could be particularly susceptible to negative effects due to their large habitat requirements and sensitivity to anthropogenic disturbance. Given the rapid expansion of oil and gas development in many parts of the range of Ferruginous Hawks, it is critical to evaluate habitat use in both a pre-construction and post-construction environment. Understanding selection of habitat resources and nest sites, as well as the factors that contribute to home range estimates, nest success and nest productivity could help inform efforts to mitigate against potential negative effects of land use change. In my first chapter, I aimed to investigate factors associated with breeding Ferruginous Hawk home range estimates and habitat selection in a landscape slated for energy development. In a sagebrush-steppe study site in western Wyoming, I captured breeding hawks and used radio and satellite-telemetry to collect location data, estimate home range estimates, and model habitat selection. Home range estimates were smaller for females and hawks with egg-laying breeding status, and larger with increasing numbers of producing wells. Ferruginous Hawks selected habitat with high terrain ruggedness, low shrub cover, and areas closer to primary prey, and avoided areas with high density of wells. The relationship between lagomorph density and distance to development was dependent on scale. My findings show that home range estimates are smaller in my study relative to other parts of the species' range, and that future energy development is likely to reduce habitat quality and availability for Ferruginous Hawks. In my second chapter, I investigated the factors associated with nest site selection, success, and productivity in the same study site in western Wyoming. I used an existing dataset on nest site locations, nest success, and productivity, and collected new data on these response variables between 2019 and 2023. I used a resource selection function model (RSF) to evaluate nest site selection and used generalized linear mixed models (GLMMs) to evaluate nest success and productivity. Ferruginous Hawks selected nest sites in developed-open space landcover (e.g., areas cleared of vegetation with little or no infrastructure), higher topographic position index (TPI), and in closer proximity to producing wells (km). In contrast, breeding hawks avoided nest sites in areas with higher densities of producing wells (per km2) and more shrub cover (%). Nest success and productivity of egg-laying pairs was positively associated with artificial nesting platforms (ANPs) and negatively associated with anthropogenic structures and rocky outcrops, developed-open space landcover, TPI and year. These findings suggest that Ferruginous Hawks may be subject to an ecological trap when they nest on anthropogenic structures, but that ANPs are a potentially viable tool for mitigation.